Palm Oil-Based Enriched Diets for the Rotifer, Brachionus plicatilis, Improved the Growth of Asian Seabass (Lates calcarifer) Larvae - Safiin, Nik Siti Zaimah; Mustafa, Saleem; Ching, Fui Fui; Shapawi, Rossita (Frontiers in Marine Science, 2021)
Different types and inclusion levels of palm oil were incorporated in the enriched diets of L-type rotifer, Brachionus plicatilis, and fed to Asian seabass (Lates calcarifer) larvae. The dietary fish oil was replaced with either 50 or 75% of crude palm oil, CPO (CPO50, CPO75) and refined bleached deodorized palm olein, RPO (RPO50, RPO75). The enriched diet containing 100% fish oil (FO100) was used as the experimental control. Triplicate groups of the fish larvae of initial length 2.72 ± 0.14 mm were fed with enriched rotifer for 15 days. In general, palm oil-based enriched diets performed better than the control diet (FO100). Specifically, final mean body weight (31.3 ± 9.2 mg), final mean total length (11.5 ± 1.6 mm), SGR (29.0 ± 1.4%/day) and WG (7,769.4 ± 1,510.8%) of Asian seabass larvae fed RPO75 were significantly higher (P < 0.05) compared to those fed the other palm oil-based diet and FO100. The rotifer enriched with palm oil significantly affected the body proximate composition and fatty acid profiles of the fed larvae. The present study suggests that RPO and CPO can be considered as a good alternative dietary lipid for enrichment of rotifer to positively influence the nutritional requirements of the Asian seabass larvae and support their survival and growth.